A flame retardant and anti-seepage geotextile and preparation method thereof

By using flame retardant modified polypropylene fiber, plantain fiber, polyimide fiber and hydrophobic modified phosphogypsum and other materials, geotextiles with excellent flame retardant and anti-seepage properties were prepared, which solved the problem of existing geotextiles. The problems of damage and poor performance improve their service life and safety in engineering applications.

CN116289234BActive Publication Date: 2025-02-18SHANDONG TIANREN NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310299540.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2025-02-18
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

Existing geotextiles are prone to damage during use, and have poor flame retardant and anti-seepage effects, which cannot meet the needs of modern markets.

Method used

Flame-retardant modified polypropylene fiber, plantain fiber, polyimide fiber, hydrophobic modified phosphogypsum and other materials are prepared by mixing, extrusion, spinning, consolidation and thermal evaporation. and geotextile with anti-seepage properties.

Benefits of technology

It significantly improves the anti-seepage and flame retardant properties of geotextiles, extends the service life, and enhances its practicality and safety in engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116289234B_ABST
    Figure CN116289234B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of geotextiles, and discloses a flame retardant and anti-seepage geotextile and a preparation method thereof. The preparation method of the flame retardant and anti-seepage geotextile comprises the following steps: step (1) mixing flame retardant modified polypropylene fiber, plantain fiber, polyimide fiber, hydrophobically modified phosphogypsum, antioxidant, barium stearate, rubber powder, and date palm powder in a reciprocating mixing extruder to obtain a mixture; step (2) the mixture is extruded by a twin-screw extruder, filtered by a melt filter, and then spun by a melt spinning machine, and the spun fibers are evenly laid on a mesh curtain of a web forming machine, and the inclined curtain is reciprocated and laid. The net is consolidated by a needle punching machine to obtain a geotextile blank; step (3) microcrystalline wax is deposited on the surface of the geotextile blank by a thermal evaporation method to obtain a flame retardant and anti-seepage geotextile. The geotextile of the present invention has excellent flame retardant properties, anti-seepage properties, mechanical properties and antioxidant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of geotextiles, in particular to a flame retardant and impermeable geotextile and a preparation method thereof. Background Art

[0002] Geotextile, also known as geotextile, is a water-permeable geosynthetic material made of synthetic fibers through needle punching or weaving. At present, geotextile is used in the fields of road, railway drainage system, coastal engineering and protective wall. It can be built more cheaply with reinforcement, protection, drainage, filtration, isolation, anti-seepage and other functions, effectively improving the service life of the project and meeting the needs of various engineering applications. Geotextile is known as the "four major construction" materials together with cement, wood and steel. However, most of the previous geotextiles have poor use effects and are easily damaged during use, which reduces the service life of the geotextile. In addition, many geotextiles have poor flame retardant and anti-seepage effects, which cannot meet the needs of today's market, reducing the practicality and usability of geotextiles. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for preparing a flame retardant and impermeable geotextile, comprising the following steps:

[0004] Step (1) mixing flame retardant modified polypropylene fiber, plantain fiber, polyimide fiber, hydrophobically modified phosphogypsum, antioxidant, barium stearate, rubber powder, and date palm powder in a reciprocating mixing extruder at 180-220° C. for 4.0-8.0 hours to obtain a mixed material;

[0005] Step (2) the mixed material is extruded through a twin-screw extruder at 140-160° C., filtered through a melt filter, and then spun through a melt spinning machine, and the spun fibers are evenly laid on a mesh curtain of a web forming machine, and the oblique curtain is reciprocated and then consolidated through a needle punching machine to obtain a geotextile blank;

[0006] Step (3) deposits microcrystalline wax on the surface of the geotextile blank by thermal evaporation to obtain a flame retardant and impermeable geotextile.

[0007] Preferably, in step (1), the usage ratio of flame retardant modified polypropylene fiber, plantain fiber, polyimide fiber, hydrophobically modified phosphogypsum, antioxidant, barium stearate, rubber powder and date palm powder is 50-60:10-20:15-25:2.5-4.0:0.1-0.5:0.5-1.0:0.2-0.4:3.5-6.0; the antioxidant includes antioxidant 1010.

[0008] Preferably, in step (3), the amount of microcrystalline wax deposited is 0.5-2.5 wt %; the temperature of thermal evaporation is 35-45° C. and the pressure is 64-72 kPa.

[0009] Preferably, in the step (1), the phosphogypsum waste residue is ball-milled for 1.0-1.5 h at a rotation speed of 400-600 rpm and a ball-to-material ratio of 1.0-3.0:1.0, the ball-milled material is loosened, and the ball-milling is continued for 1.0-1.5 h, and the above operation is repeated 2-4 times, and then the ball-milled phosphogypsum is dried at 40-60° C., sieved through a 200-300 mesh sieve, and then calcined at 550-600° C. to obtain anhydrous phosphogypsum; at room temperature, 60-90 kg of anhydrous phosphogypsum, 30-45 kg of sodium hydroxide, and 5.0-7.5 kg of sodium sulfate are added to 300-500 kg of deionized water. , stirring at a speed of 200-400r / min for 25-45min, filtering, washing the obtained filter residue with deionized water for 3-5 times, then washing with ethanol for 3-5 times, and then drying at 50-60°C for 10-14h to obtain hydroxylated phosphogypsum; mixing 80-120kg of ethanol, 7.5-12.0kg of deionized water, and 3.2-4.8kg of stearic acid, stirring for 20-30min at a temperature of 55-65°C in a nitrogen atmosphere, and then adding 30-45kg of hydroxylated phosphogypsum, continuing the reaction for 2.0-3.0h, filtering, washing the filter residue with ethanol for 3-5 times, and drying to obtain hydrophobically modified phosphogypsum.

[0010] In the above process, anhydrous phosphogypsum is prepared by pretreating phosphogypsum waste residue, and then the surface of the anhydrous phosphogypsum is hydroxylated with a NaOH solution, and then hydrophobically modified by stearic acid, and the hydroxyl groups on the surface of the hydroxylated phosphogypsum are converted into organic long chains to obtain hydrophobically modified phosphogypsum.

[0011] Furthermore, in step (1), the method for preparing the flame retardant modified polypropylene fiber comprises the following steps:

[0012] S1: Mix NaClO2 with 35wt% HCl aqueous solution, at a wavelength of λ of 365nm and a light irradiance of 5-20mW / cm 2 irradiating under conditions of , to generate photoactivated ClO2· gas; oxidizing the dried polypropylene fiber in the photoactivated ClO2· gas to obtain surface-modified polypropylene fiber;

[0013] In the above process, carboxyl groups were introduced on the surface of polypropylene fibers by oxidation treatment in photoactivated ClO2· gas.

[0014] S2: dispersing natural halloysite nanotubes in a sodium hexametaphosphate aqueous solution to obtain pretreated halloysite nanotubes by pretreatment; mixing toluene, coupling agent KH-550, and pretreated halloysite nanotubes, heating to react, to obtain aminated halloysite nanotubes; dispersing succinic anhydride and aminated halloysite nanotubes in N,N-dimethylformamide, stirring to react, to obtain carboxylated halloysite nanotubes;

[0015] In the above process, amino groups are introduced on the surface of halloysite nanotubes by coupling agent KH-550 to obtain aminated halloysite nanotubes. The amino groups in the aminated halloysite nanotubes react with succinic anhydride to introduce carboxyl groups into the halloysite nanotubes.

[0016] S3: dispersing Ce(NO3)3·6H2O in deionized water to obtain solution A; dispersing carboxylated halloysite nanotubes in deionized water, and then adding ammonia water to adjust the pH of the solution to obtain solution B; adding solution A dropwise to solution B to react and obtain a halloysite nanotube composite material;

[0017] In the above process, the carboxyl groups in the carboxylated halloysite nanotubes coordinate with the cerium ions to form a stable chelate bond, thereby obtaining a halloysite nanotube composite material.

[0018] S4: reacting phosphoric acid with pentaerythritol to obtain pentaerythritol phosphate; dispersing melamine in methanol, adding pentaerythritol phosphate, heating, stirring and reacting to obtain an intermediate product; mixing the intermediate product, halloysite nanotube composite material, surface modified polypropylene fiber and ethanol, ultrasonicating and refluxing to obtain flame retardant modified polypropylene fiber;

[0019] In the above process, -OH in phosphoric acid reacts with -OH in pentaerythritol to obtain pentaerythritol phosphate, -OH in pentaerythritol phosphate reacts with -NH2 in melamine to obtain an intermediate product, and -NH2 in the intermediate product reacts with the carboxyl group in the halloysite nanotube composite material and the surface modified polypropylene fiber to obtain a rigid flame retardant modified polypropylene fiber with a network structure.

[0020] Preferably, in step S1, the ratio of NaClO2 to HCl aqueous solution is 40-50 g:20 L; oxidation conditions: oxidation at 60-80°C for 10-20 min.

[0021] Preferably, in the step S2, the amount of natural halloysite nanotubes added to the sodium hexametaphosphate aqueous solution is 8.0-12.0wt%; the amount ratio of toluene, coupling agent KH-550, and pretreated halloysite nanotubes is 10.0-15.0L:70.0-105L:3.0-4.5kg; heating reaction conditions: heating to 110-130°C in a nitrogen atmosphere for 20-28h; the amount ratio of succinic anhydride, aminated halloysite, and N,N-dimethylformamide is: 0.6-0.9kg:1.0-1.5kg:60-90L; stirring reaction conditions: stirring the reaction at a speed of 200-500r / min for 20-30h.

[0022] Preferably, in step S3, the ratio of Ce(NO3)3·6H2O to deionized water is 0.4-0.6kg:10-15L; the ratio of carboxylated halloysite nanotubes to deionized water is 4.5-9.0kg:100-150L; ammonia water is added to adjust the pH of the solution to 6.8-7.2; reaction conditions: react at 100-120°C for 20-30h.

[0023] Preferably, in step S4, the mass ratio of phosphoric acid, pentaerythritol and melamine is 118-177:40-60:63-95; the reaction conditions of phosphoric acid and pentaerythritol are: stirring and reacting at 200-500r / min at 20-30°C for 20-40min, and then heating to 100-120°C and maintaining for 2.5-3.5h; the reaction conditions of melamine and pentaerythritol phosphate are: stirring and reacting at 110-130°C for 2.5-3.5h; the amount ratio of the intermediate product, halloysite nanotube composite material, surface modified polypropylene fiber and ethanol is 2.5-4.5kg:30-50kg:100-120kg:600-1000L; the reflux reaction conditions are: reflux reaction at a nitrogen atmosphere at a temperature of 140-160°C and a stirring condition of 200-400r / min for 10-14h.

[0024] The flame retardant and impermeable geotextile is prepared by adopting the method for preparing the flame retardant and impermeable geotextile.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. In the present invention, hydrophobic phosphogypsum is used in synergy with polypropylene fiber, barium stearate and rubber powder to improve the anti-seepage performance of geotextile. In addition, hydrophobic phosphogypsum is not only used as a hydrophobic filler and a flame retardant filler, but more importantly, the hydrophobically modified phosphogypsum significantly improves the compatibility and interface interaction with polypropylene fiber, thereby improving the performance of polypropylene fiber. At the same time, the hydrophobically modified phosphogypsum is prepared using industrially produced phosphogypsum waste residue as raw material, thus turning waste into treasure and realizing the rational utilization of resources.

[0027] 2. In the present invention, an intermediate product with flame retardant properties is prepared. The intermediate product works together with the halloysite nanotube composite material to form a dense and coherent high-quality carbonized layer above the polypropylene surface during the combustion process, thereby obtaining polypropylene fibers with excellent flame retardant properties. The flame retardant modified polypropylene fibers and polyimide fibers are then used to prepare a geotextile with excellent flame retardant effects. Furthermore, the halloysite nanotubes in the halloysite nanotube composite material can not only improve the thermal stability and flame retardancy of polypropylene through the coking reaction during catalytic combustion, but also increase the mechanical properties of the polypropylene fibers as a rigid matrix, thereby improving the mechanical properties of the geotextile. The Ce in the halloysite nanotube composite material is connected to the flame retardant component through chemical bonds as a flame retardant synergist, and then cooperates with other components to exert a better flame retardant effect.

[0028] 3. The plantain fiber and date palm powder in the present invention can cooperate with other components such as barium stearate, rubber powder, antioxidant, flame retardant modified polypropylene fiber, etc. to further improve the mechanical properties and antioxidant properties of the geotextile. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a process flow chart of the preparation of the flame retardant and impermeable geotextile of the present invention;

[0030] Figure 2 It is a comparison chart of limiting oxygen index test of flame retardant and impermeable geotextiles of Examples 3-5 and Comparative Examples 1-5 in the present invention;

[0031] Figure 3 It is a comparison chart of vertical permeability coefficient test of flame retardant and impermeable geotextiles of Examples 3-5 and Comparative Examples 1-5 in the present invention;

[0032] Figure 4 It is a comparison chart of the CBR bursting strength test of the flame retardant and impermeable geotextiles of Examples 3-5 and Comparative Examples 1-5 in the present invention;

[0033] Figure 5 is a schematic diagram of the synthesis of the halloysite nanotube composite material of the present invention;

[0034] Figure 6 It is a schematic diagram of the synthesis of the intermediate product of the present invention. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] This embodiment discloses a method for preparing hydrophobically modified phosphogypsum, comprising the following steps:

[0038] The phosphogypsum waste residue was ball-milled for 1.3 h at a rotation speed of 500 rpm and a ball-to-material ratio of 2.0:1, the ball-milled material was loosened, and the ball-milling was continued for 1.3 h. The above operation was repeated 3 times, and then the ball-milled phosphogypsum was dried at 50°C, passed through a 250-mesh sieve, and calcined at 580°C to obtain anhydrous phosphogypsum; at room temperature, 75 kg of anhydrous phosphogypsum, 38 kg of sodium hydroxide, and 6.5 kg of sodium sulfate were added to 400 kg of deionized water and spun at 300 r / m in speed and stirred for 35 min, filtered, the obtained filter residue was first washed with deionized water 4 times, then washed with ethanol 4 times, and then dried at 55 ° C for 12 h to obtain hydroxylated phosphogypsum; 100 kg of ethanol, 9.5 kg of deionized water, and 4.0 kg of stearic acid were mixed, stirred for 25 min at 60 ° C in a nitrogen atmosphere, and then 38.5 kg of hydroxylated phosphogypsum was added, the reaction was continued for 2.5 h, filtered, the filter residue was washed with ethanol 4 times, and dried to obtain hydrophobically modified phosphogypsum.

[0039] Example 2

[0040] This embodiment discloses a method for preparing a flame retardant modified polypropylene fiber, comprising the following steps:

[0041] S1: NaClO2 and 35wt% HCl aqueous solution were mixed in a dosage ratio of 45g:20L, and the wavelength λ was 365nm and the light irradiance was 15mW / cm 2 The polypropylene fiber was irradiated under conditions of 100 ℃ to generate photoactivated ClO2· gas; the polypropylene fiber was washed with deionized water and then dried; the dried polypropylene fiber was oxidized in photoactivated ClO2· gas at 70 ℃ for 15 minutes, and then washed with deionized water and vacuum dried at 25 ℃ to obtain surface modified polypropylene fiber.

[0042] S2: Disperse natural halloysite nanotubes in a 0.05wt% sodium hexametaphosphate aqueous solution at an addition amount of 10.0wt%, ultrasonicate for 30min, let stand for 20min, take the upper liquid, wash it with deionized water 4 times, and vacuum dry it at 50°C for 6.0h to obtain pretreated halloysite nanotubes; mix 12.5L toluene, 87.5L coupling agent KH-550, and 3.8kg pretreated halloysite nanotubes, heat to 120°C for reaction for 24h under a nitrogen atmosphere, wash the reaction product with toluene and ethanol 4 times each, and vacuum dry it at 40°C for 9.0h to obtain amino halloysite nanotubes; disperse 0.8kg succinic anhydride and 0.8kg amino halloysite nanotubes in 75L N,N-dimethylformamide, stir and react at a speed of 350r / min for 25h, centrifuge, wash, and vacuum dry at 40°C for 9.0h to obtain carboxylated halloysite nanotubes.

[0043] S3: Disperse 0.5 kg of Ce(NO3)3·6H2O in 12.5 L of deionized water to obtain solution A; disperse 6.8 kg of carboxylated halloysite nanotubes in 125 L of deionized water, stir until uniform, and then add ammonia water to adjust the pH of the solution to 7.0 to obtain solution B; add solution A dropwise to solution B, react at 110°C for 25 hours, and after the reaction is completed, cool to room temperature, centrifuge, wash the centrifuged product 4 times with deionized water, and vacuum dry at 100°C to constant weight to obtain a halloysite nanotube composite material.

[0044] S4: Phosphoric acid and pentaerythritol were mixed in a mass ratio of 148:50, stirred at 25°C at a speed of 350 r / min for 30 min, and then heated to 110°C for 3.0 h to obtain pentaerythritol phosphate; 79 kg of melamine was dispersed in 700 L of methanol at 25°C, pentaerythritol phosphate was added, the temperature was raised to 120°C, stirred for 3.0 h, filtered, the filter residue was washed with methanol, and dried at 70°C for 3.0 h to obtain an intermediate product; 3.5 k g intermediate product, 40 kg halloysite nanotube composite material, 110 kg surface modified polypropylene fiber, and 800 L ethanol were mixed, ultrasonicated at a frequency of 30 kHz for 45 min, and then refluxed for 12 h under a nitrogen atmosphere at a temperature of 150 ° C and a stirring speed of 300 r / min. After the reaction was completed, it was cooled to room temperature, filtered, and the filter residue was washed with deionized water, and then dried at 45 ° C for 11 h and then at 90 ° C for 11 h to obtain flame retardant modified polypropylene fiber.

[0045] Example 3

[0046] This embodiment discloses a method for preparing a flame retardant and impermeable geotextile, comprising the following steps:

[0047] Step (1) 50 parts of flame retardant modified polypropylene fiber, 10 parts of plantain fiber, 15 parts of polyimide fiber, 2.5 parts of hydrophobically modified phosphogypsum, 0.1 parts of antioxidant 1010, 0.5 parts of barium stearate, 0.2 parts of rubber powder, and 3.5 parts of date palm powder are weighed in parts by weight and mixed in a reciprocating mixing extruder at 180° C. for 4.0 hours to obtain a mixed material.

[0048] Step (2) The mixed material is extruded through a twin-screw extruder with a screw temperature of 140°C, filtered through a melt filter, and then spun using a melt spinning machine. The spun fibers are evenly laid on a mesh curtain of a web-forming machine. After the oblique curtain is reciprocated and laid, they are consolidated by a needle punching machine to obtain a geotextile blank, which is then laid flat on a metal frame for standby use.

[0049] Step (3) deposits 0.5 wt % microcrystalline wax on the surface of the geotextile blank by thermal evaporation at a temperature of 35° C. and a pressure of 64 kPa to obtain a flame retardant and impermeable geotextile.

[0050] Example 4

[0051] This embodiment discloses a method for preparing a flame retardant and impermeable geotextile, comprising the following steps:

[0052] Step (1) 60 parts of flame retardant modified polypropylene fiber, 20 parts of plantain fiber, 25 parts of polyimide fiber, 4.0 parts of hydrophobically modified phosphogypsum, 0.5 parts of antioxidant 1010, 1.0 parts of barium stearate, 0.4 parts of rubber powder, and 6.0 parts of date palm powder are weighed in parts by weight and mixed in a reciprocating mixing extruder at 220° C. for 8.0 hours to obtain a mixed material.

[0053] Step (2) The mixed material is extruded through a twin-screw extruder with a screw temperature of 160°C, filtered through a melt filter, and then spun using a melt spinning machine. The spun fibers are evenly laid on a mesh curtain of a web-forming machine. After the oblique curtain is reciprocated and laid, they are consolidated by a needle punching machine to obtain a geotextile blank, which is then laid flat on a metal frame for standby use.

[0054] Step (3) deposits 2.5 wt% microcrystalline wax on the surface of the geotextile blank by thermal evaporation at a temperature of 45° C. and a pressure of 72 kPa to obtain a flame retardant and impermeable geotextile.

[0055] Example 5

[0056] This embodiment discloses a method for preparing a flame retardant and impermeable geotextile, comprising the following steps:

[0057] Step (1) 55 parts of flame retardant modified polypropylene fiber, 15 parts of plantain fiber, 20 parts of polyimide fiber, 3.2 parts of hydrophobically modified phosphogypsum, 0.3 parts of antioxidant 1010, 0.7 parts of barium stearate, 0.3 parts of rubber powder, and 4.7 parts of date palm powder are weighed in parts by weight and mixed in a reciprocating mixing extruder at 200° C. for 6.0 hours to obtain a mixed material.

[0058] Step (2) The mixed material is extruded through a twin-screw extruder with a screw temperature of 150°C, filtered through a melt filter, and then spun using a melt spinning machine. The spun fibers are evenly laid on a mesh curtain of a web-forming machine. After the oblique curtain is reciprocated and laid, they are consolidated by a needle punching machine to obtain a geotextile blank, which is then laid flat on a metal frame for standby use.

[0059] Step (3) deposits 1.5 wt% microcrystalline wax on the surface of the geotextile blank by thermal evaporation at a temperature of 40° C. and a pressure of 68 kPa to obtain a flame retardant and impermeable geotextile.

[0060] Comparative Example 1

[0061] Comparative Example 1 Compared with Example 5, polypropylene fiber is used instead of flame retardant modified polypropylene fiber in the flame retardant and anti-seepage geotextile in Comparative Example 1, and other conditions remain unchanged.

[0062] Comparative Example 2

[0063] Compared with Example 5, in Comparative Example 2, phosphogypsum is used instead of hydrophobic modified phosphogypsum in the flame retardant and anti-seepage geotextile in Comparative Example 2, and other conditions remain unchanged.

[0064] Comparative Example 3

[0065] Comparative Example 3 Compared with Example 5, no plantain fiber was added to the flame retardant and anti-seepage geotextile in Comparative Example 3, and other conditions remained unchanged.

[0066] Comparative Example 4

[0067] Comparative Example 4 Compared with Example 5, no date palm powder was added to the flame retardant and anti-seepage geotextile in Comparative Example 4, and other conditions remained unchanged.

[0068] Comparative Example 5

[0069] Comparative Example 5 Compared with Example 5, the flame retardant and anti-seepage geotextile in Comparative Example 5 is not deposited with microcrystalline wax, and other conditions remain unchanged.

[0070] The hydrophobically modified phosphogypsum and the flame retardant modified polypropylene fiber in Examples 3-5 and Comparative Examples 1-5 come from the hydrophobically modified phosphogypsum prepared in Example 1 and the flame retardant modified polypropylene fiber prepared in Example 2, respectively.

[0071] Experimental example

[0072] The flame retardant properties, anti-seepage properties and mechanical properties of the flame retardant and anti-seepage geotextiles prepared in Examples 3-5 and Comparative Examples 1-5 were tested.

[0073] 1. Flame retardancy test:

[0074] 1) Vertical burning rating test: According to the standard test method ASTM D 3801 (2021), a vertical burning test is performed using a UL94 instrument.

[0075] 2) Oxygen index test: Oxygen index meter was used to measure according to standard test method ISO 4589-2: (2017). The test results are shown in Table 1:

[0076] Table 1

[0077]

[0078] From the test results in Table 1, it can be seen that the flame retardant and anti-seepage geotextiles prepared in Examples 3-5 of the present invention have excellent flame retardant properties. From the comparison between Comparative Example 1 and Example 5, it can be seen that the flame retardant modified polypropylene fiber prepared in the present invention has better flame retardant properties than ordinary polypropylene fibers, and can further improve the flame retardant properties of geotextiles; from the comparison between Comparative Example 2 and Example 5, it can be seen that the phosphogypsum in the present invention can also improve the flame retardant properties of geotextiles.

[0079] 2. Anti-seepage performance test: The test was conducted in accordance with GB / T15789-2005 "Determination of vertical permeability characteristics of geotextiles and related products without load". The test results are shown in Table 2:

[0080] Table 2

[0081]

[0082] It can be seen from the test results in Table 2 that the flame retardant and anti-seepage geotextiles prepared in Examples 3-5 of the present invention have excellent anti-seepage performance. From the comparison between Comparative Example 2 and Example 5, it can be seen that the hydrophobic modified phosphogypsum prepared in the present invention can further improve the anti-seepage performance of the geotextile; from the comparison between Comparative Example 5 and Example 5, it can be seen that the geotextile treated with microcrystalline wax deposition has better anti-seepage performance.

[0083] 3. Mechanical properties test: The YT010-1000 electronic geotextile comprehensive strength tester was used to test the bursting strength in accordance with GB / T14800-2010 "Geosynthetics static bursting test (CBR method)". The test results are shown in Table 3:

[0084] Table 3

[0085]

[0086] From the test results in Table 2, it can be seen that the CBR bursting strength of the flame retardant and impermeable geotextiles prepared in Examples 3-5 of the present invention is above 10.5 / KN. From the comparison between Comparative Example 1 and Example 5, it can be seen that the rigid flame retardant modified polypropylene fiber prepared in the present invention improves the mechanical properties of the polypropylene fiber, thereby improving the mechanical properties of the geotextile; from the comparison between Comparative Example 2 and Example 5, it can be seen that the hydrophobic modified phosphogypsum improves the interface interaction between the phosphogypsum and the polypropylene fiber, thereby improving the mechanical properties of the geotextile; from the comparison between Comparative Examples 3-4 and Example 5, it can be seen that the addition of plantain fiber and date palm powder also has a positive effect on the improvement of the mechanical properties of the geotextile.

[0087] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a flame retardant and impermeable geotextile, characterized in that: The following steps are involved: Step (1) mixing flame retardant modified polypropylene fiber, psyllium fiber, polyimide fiber, hydrophobically modified phosphogypsum, antioxidant, barium stearate, rubber powder and date palm powder in a reciprocating mixing extruder at 180-220° C. for 4.0-8.0 hours to obtain a mixed material; the amount ratio of flame retardant modified polypropylene fiber, psyllium fiber, polyimide fiber, hydrophobically modified phosphogypsum, antioxidant, barium stearate, rubber powder and date palm powder is 50-60:10-20:15-25:2.5-4.0:0.1-0.5:0.5-1.0:0.2-0.4:3.5-6.0; The preparation method of hydrophobically modified phosphogypsum comprises: preparing anhydrous phosphogypsum by pre-treating phosphogypsum waste residue, then hydroxylating the surface of the anhydrous phosphogypsum with a NaOH solution, and then hydrophobically modifying the surface of the anhydrous phosphogypsum with stearic acid, so that the hydroxyl groups on the surface of the hydroxylated phosphogypsum are converted into organic long chains to obtain the hydrophobically modified phosphogypsum; The preparation method of flame-retardant modified polypropylene fiber comprises: introducing carboxyl groups on the surface of polypropylene fiber by oxidation treatment in photoactivated ClO2 gas; introducing amino groups on the surface of halloysite nanotubes by coupling agent KH-550 to obtain amination halloysite nanotubes, reacting the amino groups in the amination halloysite nanotubes with succinic anhydride to introduce carboxyl groups in the halloysite nanotubes; coordinating the carboxyl groups in the carboxylated halloysite nanotubes with cerium ions to form stable chelate bonds to obtain halloysite nanotube composite materials; reacting phosphoric acid with -OH of pentaerythritol to obtain pentaerythritol phosphate, reacting the phosphoric acid group in the pentaerythritol phosphate with -NH2 in melamine to obtain an intermediate product, reacting the -NH2 in the intermediate product with the carboxyl groups in the halloysite nanotube composite material and the surface-modified polypropylene fiber to obtain a flame-retardant modified polypropylene fiber with a network structure and rigidity; Step (2) the mixed material is extruded through a twin-screw extruder at 140-160° C., filtered through a melt filter, and then spun through a melt spinning machine, and the spun fibers are evenly laid on a mesh curtain of a web forming machine, and the oblique curtain is reciprocated and then consolidated through a needle punching machine to obtain a geotextile blank; Step (3) deposits microcrystalline wax on the surface of the geotextile blank by thermal evaporation to obtain a flame retardant and impermeable geotextile.

2. The method for preparing the flame retardant and impermeable geotextile according to claim 1, characterized in that: In the step (1), the antioxidant includes antioxidant 1010.

3. The method for preparing the flame retardant and impermeable geotextile according to claim 1, characterized in that: In the step (3), the amount of microcrystalline wax deposited is 0.5-2.5wt%; the temperature of thermal evaporation is 35-45°C and the pressure is 64-72kPa.

4. The method for preparing the flame retardant and impermeable geotextile according to claim 1, characterized in that: In the step (1), the preparation method of the hydrophobically modified phosphogypsum comprises: subjecting the phosphogypsum waste residue to ball milling, drying it at 40-60°C, passing it through a 200-300 mesh sieve, and then calcining it at 550-600°C to obtain anhydrous phosphogypsum; at room temperature, adding 60-90 kg of anhydrous phosphogypsum, 30-45 kg of sodium hydroxide, and 5.0-7.5 kg of sodium sulfate to 300-500 kg of deionized water, and rotating at 200-400 r / min. The mixture is stirred at a low speed for 25-45 minutes, filtered, washed and dried to obtain hydroxylated phosphogypsum; 80-120 kg of ethanol, 7.5-12.0 kg of deionized water and 3.2-4.8 kg of stearic acid are mixed, stirred for 20-30 minutes at a temperature of 55-65°C in a nitrogen atmosphere, and then 30-45 kg of hydroxylated phosphogypsum is added, and the reaction is continued for 2.0-3.0 hours, filtered, washed and dried to obtain hydrophobically modified phosphogypsum.

5. The method for preparing the flame retardant and impermeable geotextile according to claim 1, characterized in that: In the step (1), the method for preparing the flame retardant modified polypropylene fiber comprises the following steps: S1: Mix NaClO2 with 35wt% HCl aqueous solution, at a wavelength of λ of 365nm and a light irradiance of 5-20mW / cm 2 irradiating under conditions of , to generate photoactivated ClO2· gas; oxidizing the dried polypropylene fiber in the photoactivated ClO2· gas to obtain surface-modified polypropylene fiber; S2: dispersing natural halloysite nanotubes in a sodium hexametaphosphate aqueous solution to obtain pretreated halloysite nanotubes by pretreatment; mixing toluene, coupling agent KH-550, and pretreated halloysite nanotubes, heating to react, to obtain aminated halloysite nanotubes; dispersing succinic anhydride and aminated halloysite nanotubes in N,N-dimethylformamide, stirring to react, to obtain carboxylated halloysite nanotubes; S3: dispersing Ce(NO3)3·6H2O in deionized water to obtain solution A; dispersing carboxylated halloysite nanotubes in deionized water, and then adding ammonia water to adjust the pH of the solution to obtain solution B; adding solution A dropwise to solution B to react and obtain a halloysite nanotube composite material; S4: reacting phosphoric acid with pentaerythritol to obtain pentaerythritol phosphate; dispersing melamine in methanol, adding pentaerythritol phosphate, heating, stirring and reacting to obtain an intermediate product; mixing the intermediate product, halloysite nanotube composite material, surface modified polypropylene fiber and ethanol, ultrasonicating and refluxing to obtain flame retardant modified polypropylene fiber.

6. The method for preparing the flame retardant and impermeable geotextile according to claim 5, characterized in that: In the step S1, the ratio of NaClO2 to HCl aqueous solution is 40-50 g:20 L; oxidation conditions: oxidation at 60-80°C for 10-20 min.

7. The method for preparing the flame retardant and impermeable geotextile according to claim 5, characterized in that: In the step S2, the amount of natural halloysite nanotubes added to the sodium hexametaphosphate aqueous solution is 8.0-12.0wt%; the amount ratio of toluene, coupling agent KH-550, and pretreated halloysite nanotubes is 10.0-15.0L:70.0-105L:3.0-4.5kg; the heating reaction conditions are: heated to 110-130°C in a nitrogen atmosphere and reacted for 20-28h; the amount ratio of succinic anhydride, aminated halloysite, and N,N-dimethylformamide is: 0.6-0.9kg:1.0-1.5kg:60-90L; the stirring reaction conditions are: stirring the reaction at a speed of 200-500r / min for 20-30h.

8. The method for preparing the flame retardant and impermeable geotextile according to claim 5, characterized in that: In the step S3, the usage ratio of Ce(NO3)3·6H2O to deionized water is 0.4-0.6kg:10-15L; the usage ratio of carboxylated halloysite nanotubes to deionized water is 4.5-9.0kg:100-150L; ammonia water is added to adjust the pH of the solution to 6.8-7.2; reaction conditions: react at 100-120°C for 20-30h.

9. The method for preparing the flame retardant and impermeable geotextile according to claim 5, characterized in that: In the step S4, the mass ratio of phosphoric acid, pentaerythritol and melamine is 118-177:40-60:63-95; the reaction conditions of phosphoric acid and pentaerythritol are: stirring and reacting at 200-500r / min at 20-30°C for 20-40min, and then heating to 100-120°C and maintaining for 2.5-3.5h; the reaction conditions of melamine and pentaerythritol phosphate are: stirring and reacting at 110-130°C for 2.5-3.5h; the amount ratio of the intermediate product, halloysite nanotube composite material, surface modified polypropylene fiber and ethanol is 2.5-4.5kg:30-50kg:100-120kg:600-1000L; the reflux reaction conditions are: reflux reaction at a nitrogen atmosphere at a temperature of 140-160°C and a stirring condition of 200-400r / min for 10-14h.

10. A flame retardant and impermeable geotextile prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Halloysite-containing nanotube halogen-free intumescent flame retardant and preparation method and application thereof

    CN107163375A

  • Nanometer flame-retardant material for garment production and preparation technology thereof

    CN109337366A

  • Flame-retardant fabric and preparation method thereof

    CN114541034A

  • Fire retardant nonwoven material and process for manufacture

    US20080050565A1